Smartphone-mediated communication and mental health: the moderating role of social support among university students in Makassar, Indonesia - Riyadi, Riyadi; Fatimah, Jeanny Maria; Hasrulah, Hasrullah (Frontiers in Human Dynamics, 2025)
IntroductionThis study examines the relationship between smartphone use and mental health among undergraduate students in Makassar, Indonesia, with particular attention to the moderating role of social support. The investigation is grounded in the Stress-Buffering Hypothesis and Uses and Gratifications Theory within the collectivistic cultural context of Indonesia.MethodsA stratified random sample of 400 undergraduate students from three universities in Makassar was surveyed. Standardized instruments were employed, including the Smartphone Use Scale, the Depression Anxiety Stress Scale (DASS-21), and the Multidimensional Scale of Perceived Social Support. Correlation and moderation analyses were conducted to test the study hypotheses.ResultsFindings reveal that general smartphone use showed only a weak positive correlation with psychological distress (r = 0.12, p < 0.05). In contrast, compulsive smartphone use demonstrated a stronger association with symptoms of depression, anxiety, and stress (r = 0.28, p < 0.001). Social support displayed a robust negative correlation with distress (r = −0.34, p < 0.001) and significantly moderated the negative effects of smartphone use on mental health (β = −0.09, p < 0.05).DiscussionThe results provide tentative support for extending existing theoretical frameworks into smartphone-mediated interactions among students in collectivistic contexts. Although the moderation effect of social support was modest and should be interpreted with caution, the findings highlight the practical importance of enhancing peer and community-based interventions to reduce risks associated with compulsive smartphone use. Limitations include the restriction of the sample to undergraduate students in Makassar, indicating the need for future research across different regions and age groups in Indonesia.